A novel regulatory facet for hypertriglyceridemia: The role of microRNAs in the regulation of triglyceride-rich lipoprotein biosynthesis. (January 2023) - Khalifeh, Masoumeh; Santos, Raul D.; Oskuee, Reza Kazemi; Badiee, Ali; Aghaee-Bakhtiari, Seyed Hamid; Sahebkar, Amirhossein
Abstract: Atherosclerotic cardiovascular disease (ASCVD) is one of the major leading global causes of death. Genetic and epidemiological studies strongly support the causal association between triacylglycerol-rich lipoproteins (TAGRL) and atherogenesis, even in statin-treated patients. Recent genetic evidence has clarified that variants in several key genes implicated in TAGRL metabolism are strongly linked to the increased ASCVD risk. There are several triacylglycerol-lowering agents; however, new therapeutic options are in development, among which are miRNA-based therapeutic approaches. MicroRNAs (miRNAs) are small non-coding RNAs (18–25 nucleotides) that negatively modulate gene expression through translational repression or degradation of target mRNAs, thereby reducing the levels of functional genes. MiRNAs play a crucial role in the development of hypertriglyceridemia as several miRNAs are dysregulated in both synthesis and clearance of TAGRL particles. MiRNA-based therapies in ASCVD have not yet been applied in human trials but are attractive. This review provides a concise overview of current interventions for hypertriglyceridemia and the development of novel miRNA and siRNA-based drugs. We summarize the miRNAs involved in the regulation of key genes in the TAGRLs synthesis pathway, which has gained attention as a novel target for therapeutic applications in CVD.